Multidrug-Resistant Tuberculosis in Central Asia and Predominant Beijing Lineage, Challenges in Diagnosis, Treatment Barriers, and Infection Control Strategies: An Integrative Review - Ulan Kozhamkulov; Sholpan Iglikova; Anar Rakisheva; Joseph Almazan (Antibiotics)
Background: Multidrug-resistant tuberculosis (MDR-TB) remains a significant public health threat in Central Asia, where rising resistance to first-line anti-TB drugs challenges control efforts. As of 2024, the World Health Organization (WHO) reports that over 2.5% of new TB cases and 18% of previously treated cases are resistant to first-line TB drugs worldwide. Objectives: This integrative review synthesizes current evidence on MDR-TB in Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan, with a focus on infection control, diagnostic advancements, and evolving treatment strategies. Methods: A comprehensive literature search was conducted across five electronic databases: PubMed, Scopus, Web of Science, Embase, World Health Organization (WHO) Global Tuberculosis Database, and ClinicalTrials.gov. A total of 29 articles from Central Asian countries met the inclusion criteria. Results: Four main themes were identified: “genetic variability and resistance patterns of MDR-TB strains”; “barriers to effective treatment”; “diagnostic tools”, and “infection control strategies”. Conclusions: This review underscores the importance of comprehensive, multifactorial approaches in addressing drug-resistant TB in the region. The implementation of early diagnosis and all-oral treatment regimens has improved adherence in recent studies.